Comparison of autologous osteoperiosteal cylinder and osteochondral graft transplantation in the treatment of large cystic osteochondral lesions of the talus (OLTs): a protocol for a non-inferiority randomised controlled trial. Issue 2 (9th February 2020) - Deng, En; Shi, Weili; Jiang, Yanfang; Guo, Qinwei
Abstract : Introduction: Large cystic osteochondral lesions of the talus (OLTs) have been shown to have inferior clinical outcomes after reparative techniques such as bone marrow stimulation. Autologous osteochondral transplantation has been viewed as an alternative choice for treating these lesions, but donor-site morbidity has limited its application. Excellent clinical outcomes have been shown in repairing these types of lesions with autologous osteoperiosteal grafts, and these outcomes are achieved at a low cost and without donor-site morbidity in the normal knee joint. This will be the first randomised controlled trial to compare the two surgical techniques, and recommendations for the treatment of patients with large cystic OLTs will be provided. Methods and analysis: A non-inferiority randomised controlled trial will be conducted. A total of 70 participants with clinically diagnosed large cystic OLTs will be randomly allocated to either the experimental group or the control group at a ratio of 1:1. The experimental group will be treated with autologous osteoperiosteal cylinder graft transplantation, while the control group will be treated with autologous osteochondral transplantation. The primary outcome measure will be the American Orthopaedic Foot & Ankle Society Ankle-Hindfoot Score and the Short Form 12 (SF-12) questionnaire. Secondary outcome measures will include the secondary arthroscopy International Cartilage Repair Society score, the Magnetic Resonance Observation of Cartilage Repair Tissue score, the Tegner activity level score, the visual analogue scale, routine X-rays, CT and complications. These parameters will be evaluated preoperatively, as well as at 3, 6, 12, 24, 36 and 60 months postoperatively. In this trial, we hypothesised that both procedures offer good results for the treatment of patients with large cystic OLTs, and occurrence of donor-site morbidity in autologous osteoperiosteal cylinder graft transplantation group is less than that in autologous osteochondral transplantation group. Ethics and dissemination: The current study was approved by the board of research ethics of Peking University Third Hospital Medical Science Research Ethics Committee. The results of this study will be presented at national and international conferences and published in peer-reviewed journals. Trial registration number: NCT03347877 .